The Importance of School Crafts Programs to Increase Student Creativity: Literature Review - Pitaloka, Dyah Ayu; Muhid, Abdul (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
Creativity is the capacity of an individual to generate innovative and valuable ideas or products that result from imaginative thinking or the synthesis of diverse thoughts and not merely by summarizing previous information. This creative ability can be fostered and nurtured through the school's craft program, which is an extensive program that trains students to use natural resources to create artistic works. Craft activities aim to develop students into independent, creative, and innovative individuals who can create art that is both interesting and beneficial to their environment. The research methodology used in this study is a comprehensive literature review, which involved searching through databases such as Researchgate and Google Scholar for relevant articles and books, both print and online. The findings suggest that the school craft program can be an effective tool for enhancing student creativity. It provides space for students to explore their imaginations and innovate freely.